Characteristics and Perceptions of the Community Regarding National Health Insurance in the Participation - Agnes Napitupulu; Crismis Novalinda Ginting; Ali Napiah Nasution (Postgraduate, University of Mataram, 2023)
This study aims to examine and analyze the characteristics and perceptions of the community regarding the National Health Insurance (Jaminan Kesehatan Nasional or JKN) in Toba district, as well as the participation of individuals in the JKN program. The research methodology employed in this study is quantitative in nature, utilizing a cross-sectional design. The population for this study consisted of 206,199 individuals, and the sampling technique employed was the Slovin method, resulting in a sample size of 399 participants. Based on the test results, there is a relationship between age and the community's perception of the national health insurance program (JKN) and their participation as JKN participants in Toba district. Gender also has a relationship with participation in the National Health Insurance program. The number of family members is also related to participation in the National Health Insurance program. Knowledge is associated with participation in the National Health Insurance program. The current needs of the community are related to participation in the National Health Insurance program. Expectations are associated with participation in the National Health Insurance program. Perceived product quality is also related to participation in the National Health Insurance program.